Magnitude, Specificity, and Avidity of Sporozoite-Specific Antibodies Associate With Protection Status and Distinguish Among RTS, S/AS01 Dose Regimens. (30th December 2020) - Dennison, S Moses; Reichartz, Matthew; Abraha, Milite; Spreng, Rachel L; Wille-Reece, Ulrike; Dutta, Sheetij; Jongert, Erik; Alam, S Munir; Tomaras, Georgia D
Abstract: Background: The malaria vaccine, RTS, S/AS01, demonstrated an enhanced efficacy (86.7%) in a delayed third fractional dose (0.1.7Fx) regimen in controlled human malaria infection trials compared with a standard full-dose (0.1.2) regimen (62.5%). To understand the humoral component of the RTS, S/AS01 vaccine-induced protection against sporozoite infection in these 2 regimens, we investigated the serum antibody dynamics of 0.1.2 and 0.1.7Fx groups vaccinees. Methods: The specific binding responses (magnitude) and dissociation rates (avidity) of serum antibodies interaction with a recombinant Plasmodium falciparum circumsporozoite protein (CSP) and peptides corresponding to the central repeat region (NANP6), the C-terminal region (PF16), and the N-terminal junction (N-interface) of CSP, respectively, were measured using a Biolayer Interferometry assay. Results: On the day of challenge, higher NANP6-specific antibody responses were associated with protection in the 0.1.2 group. In contrast, slower antibody dissociation rates for CSP and PF16 binding were observed in the protected 0.1.7Fx group. Protected vaccinees of both groups exhibited 2- to 3-fold higher N-interface peptide binding antibody responses. Conclusions: Unlike the standard dose, the delayed-fractional third dose of RTS, S/AS01 induced higher avidity CSP and PF16 binding antibodies that were associated with protection against sporozoite infection. Abstract : Antibody dynamics in 2 regimens of RTS, S/AS01 vaccinees were examined by a Biolayer Interferometry assay. Results highlight the interregimen differences in antibody specificity, magnitude, and avidity and identified trends associated with protection against controlled human malaria infection.